Commodification of Social Media: Digitization of Religion as a Contemporary Da'wah Media - Ahmad Rizal, Derry; Khorina Seci Vella, Nurul (BELIEF: Sociology of Religion Journal, 2024)
The fast-paced development of technology has made it a necessity in society. Without exception, social media, especially for Generation Z always depends on a variety of social media. This development extends to the religious world, namely making some social media as contemporary da'wah media. In the period of time, the shift of da'wah in electronic media occurred in the 2000s, namely through radio, television, and other media. This research uses the netnography method, which looks at the consumptive culture based on cyberspace or online. In this research search, a variety of social media are popular among Generation Z, such as Instagram, TikTok, and YouTube. The content of Instagram @halimahalaydrus, for example, can be seen as the account only presents religious sentences and images that relate to today's society. This also happens in TikTok, bringing up pieces of videos about contemporary da'wah such as that performed by Gus Iqdam in account @Gus Iqdam Official. Some of these views show da'wah in a contemporary way by utilizing popular social media.